2012
DOI: 10.1007/s11414-012-9288-9
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Communication Between Primary Health Care and Mental Health Care: An Examination of Referral and Discharge Letters

Abstract: In managing treatment for persons with mental illness, the primary care physician (PCP) needs to communicate with mental health (MH) professionals in various settings over time to provide appropriate management and continuity of care. However, effective communication between PCPs and MH specialists is often poor. The present study reviewed evidence on the quality of information transfer between PCPs and specialist MH providers for referral requests and after inpatient discharge. Twenty-three audit studies were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
81
1
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 46 publications
2
81
1
9
Order By: Relevance
“…Research has shown that a structured referral form can improve the quality of referrals and indeed communication between GPs and mental health professionals. Following their review of 23 audits assessing quality of referrals and nine audits assessing strategies to improve quality, which showed limited evidence overall, Durbin et al (2012) identified positive results using structured forms, advising that for optimal outcomes these should include a 'minimum set of items, definition of items and structure to hold these information'. The study by Craven & Bland (2006) showed in a systematic review that enhanced collaboration paired with treatment guidelines or protocols offers important benefits over either intervention alone in major depression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research has shown that a structured referral form can improve the quality of referrals and indeed communication between GPs and mental health professionals. Following their review of 23 audits assessing quality of referrals and nine audits assessing strategies to improve quality, which showed limited evidence overall, Durbin et al (2012) identified positive results using structured forms, advising that for optimal outcomes these should include a 'minimum set of items, definition of items and structure to hold these information'. The study by Craven & Bland (2006) showed in a systematic review that enhanced collaboration paired with treatment guidelines or protocols offers important benefits over either intervention alone in major depression.…”
Section: Discussionmentioning
confidence: 99%
“…As a practical step, we suggest involving GPs in designing an online version of the referral pro forma. This should be made easily accessible and should include tables and prompts for the required information (Durbin et al 2012). A re-audit within 1 year would be important in order to monitor and sustain improvement.…”
Section: Discussionmentioning
confidence: 99%
“…At epikriser og overføringsnotat mangler viktig informasjon kan medføre mangelfull kommunikasjon mellom sykehus og oppfølgende instans. Dette kan få negative behandlingsmessige konsekvenser (Durbin et al, 2012), uhell og alvorlige hendelser (Lenert et al, 2014). Inntrykket fra epikrisene i vår studie var at selvmordsrisikovurderingene i varierende grad var tydelige, de inneholdt i liten eller ingen grad begrunnelse for selve vurderingen, de var ofte korte og uten ensartet begrepsbruk.…”
Section: Suicidologi Nr 3/2016unclassified
“…Selvmordsrisiko vurderes til å vaere lik det den er i hennes habitual tilstand» illustrerer hvordan uklart språk kan skape usikkerhet dersom behandler ved oppføl-gende instans ikke kjenner pasienten fra før. Epikrisens språk bør vaere eksplisitt med entydig begrepsbruk slik at potensielle misforståelser unngås (Durbin, et al, 2012). Epikriseinformasjon uten rom for flertydig tolkning kan gi økt pasientsikkerhet.…”
Section: Suicidologi Nr 3/2016unclassified
See 1 more Smart Citation